Improvement of rear bumper design - Mohd Hafizan, Mamat (2008)
Bumper is divided in two types, they are front bumper and rear bumper. Main function both of them are for absorbing impact by reducing damage and to the potential for bodily injury during an accident. Rear car bumper system has three main components. They are the fascia, energy absorber and bumper beam. The fascia is the outer cover in this system. It is attaches to the quarter panels and rear end panel of the system. The energy absorber attaches to the bumper beam. The bumper beam is mounted directly to the vehicle body. These components were reviewed for differences in shape and construction prior to being assembled to the vehicles. For this project, rear bumper of PROTON Persona car was chosen to be benchmarking. Then, the new rear bumper was design by using SOLIDWORK Software in dimensional of PROTON Persona car. By using FEA tools that is ALGOR software, the new design was analyzed at three different parts and constant force. Improvement of rear bumper design was compared based on material used, attachment, analysis on Stress Von Mises and displacement, installation, buying and repairing cost, and others. The important result is to improve rear bumper car and to give advantages to the car users such as remove and installation rear bumper knowledge